Industri Kreatif Kabupaten Bangkalan: Pendekatan Prioritas Ekonomi - Ahmad Kamil (Trunojoyo University of Madura, 2020)
At present,creative industry is considered as a sector that is able to support economic growth in the future. This study has 3 (three) objectives, first, to measure and analyze the role of Bangkalan's creative industries on employment, the number of companies, GRDP, and exports in Bangkalan. Second, Analyzing factors that influence the performance of Bangkalan's creative industries on employment, the number of companies, GRDP, exports in Bangkalan. Third, Analyze the priority determination of strategic criteria for Bangkalan's creative economy subsector. The results of this study, the strategic creative economic subsector in Bangkalan is the culinary creative economy subsector. There is a real relationship between employment with creative economic performance Bangkalan Number of companies. The number of companies has no statistical effect on Bangkalan's creative economic performance. There is a real relationship between GRDP and creative economic performance. The relationship between exports and creative economic performance is directly proportional and has a positive relationship. The determination of the priorities of the creative economy, namely the GRDP has the most priority level of contribution to the performance of the creative economy in Bangkalan.